A new gonad-infecting species of Philometra (Nematoda: Philometridae) from the Atlantic Spanish mackerel Scomberomorus maculatus (Scombridae) off the Atlantic Coast of Florida and South Carolina - Moravec, František; Bakenhaster, Micah; de Buron, Isaure (The Journal of parasitology, 2013)
A new nematode species, Philometra atlantica n. sp. (Philometridae), is described from male and female specimens found in the ovary of the Atlantic Spanish mackerel, Scomberomorus maculatus (Mitchill) (Scombridae, Perciformes), off the Atlantic coast of Florida and South Carolina. Based on light and scanning electron microscopy examination, the new species differs from most other gonad-infecting Philometra spp. in the length of spicules (111-126 μm), number and arrangement of genital papillae, and a U-shaped, dorsally interrupted caudal mound in the male. A unique feature among all gonad-infecting philometrids is the presence of 2 reflexed dorsal barbs on the distal end of the gubernaculum. From a few congeneric, gonad-infecting species with unknown males, it can be distinguished by some morphological and biometrical features found in gravid females (body length, length of first-stage larvae or esophagus, structure of caudal end) and by the host type (fish family) and geographical distribution. Philometra atlantica is the fourth valid gonad-infecting species of Philometra reported from fishes of the family Scombridae.
Keywords: Atlantský oceán; Dracunculoidea; infekce hlísticemi řádu Spirurida; Atlantic Ocean; Female; Perciformes; Prevalence; Florida; Microscopy, Electron, Scanning; Spirurida Infections; Jižní Karolína; mužské pohlaví; South Carolina; zvířata; nemoci ryb; ženské pohlaví; prevalence; Animals; Male; mikroskopie elektronová rastrovací; Fish Diseases